Definitions of serious injury in long-term residential care: a systematic review protocol - Mc Mahon, Martin (My University, 2023)
Background Evidence indicates that the reporting of serious injury in long-term residential care has increased substantially over the past decade. However, what constitutes a serious injury in residential care is poorly and inconsistently defined. This may result in incidences being unnecessarily reported as a serious injury. It is therefore, crucial to develop a consistent definition of serious injury to reduce reporting burden and to facilitate comparison between different residential care settings and across jurisdictions. This protocol describes the methods for a systematic review of existing definitions from the literature to inform the development of a consistent definition of serious injury in long-term residential care. Methods A wide range of published peer-reviewed and grey literature will be sought for this review, including guidance and policy documents. Searches will be conducted of databases including MEDLINE, CINAHL, SocINDEX, Academic Search Ultimate, and Westlaw International. Grey literature database searches will include Trip and Social Care Online. Country specific searches of government and health and social care websites will be conducted. Quality appraisal will be facilitated using the Quality Assessment for Diverse Studies (QuADS) tool and Tyndall’s checklist. The level of confidence in the findings will be assessed using the GRADE CERQual approach. A customised data extraction form will be used to extract data to reduce the risk of bias. Conceptual content analysis of data will facilitate identification of definitions of serious injury and their frequency within texts. Conclusion The findings will inform the development of a consistent definition of serious injury in long-term residential care that will reduce reporting burden, facilitate the accuracy of data collected and allow for comparison across jurisdictions. A more universal and consistent definition will enable regulators, policy makers, service providers and researchers to develop policy and practical interventions to prevent the occurrence of serious injury in long-term residential care.
PUBLISHED
Keywords: Serious injury, serious incident, adverse event, reporting, residential care, nursing homes, care homes, systematic review